Truck’s blind spot detection system / Nabila Huda Mustapa Kamal - Mustapa Kamal, Nabila Huda (2022)
Blind spots, those obscured from a driver's view in mirrors or windows, present heightened dangers for heavy vehicles like trucks and buses, given their larger blind spots compared to smaller counterparts. The alarming frequency of accidents involving heavy vehicles, often attributable to restricted visibility in these blind spot areas, underscores the critical need for effective safety solutions. This study is a direct response to this challenge, aiming to develop a blind spot detection system utilizing Arduino technology. By employing a combination of hardware and software, this system generates alerts when objects are detected near the blind spot, significantly mitigating accident risks. This innovative solution not only contributes to safety but also prioritizes the well-being of drivers. The system's outputs serve as a proactive measure, aiding in accident prevention and creating a more secure driving environment. Moreover, the integration of both hardware and software components showcases the versatility and sophistication of the proposed blind spot detection system. The multifaceted benefits extend beyond accident prevention. This system introduces a new era of driving convenience and stress reduction for operators of heavy vehicles. By addressing the challenges associated with blind spots, it transforms the driving experience into a safer, more manageable task. The implication is clear — the blind spot detection system is not just an optional addition but an essential component for enhancing road safety. In conclusion, this research underscores the pressing need for blind spot detection systems in heavy vehicles, advocating for increased attention to their incorporation. By achieving the project objectives, the implementation of this blind spot detection system emerges as a transformative force, promising a safer, more efficient future for operators of heavy vehicles on the road